Have Long-term Financial Trends Changed the Transmission of Monetary Policy? - Cournède, Boris (OECD Economics Department Working Papers, 2008)
This paper addresses the question of whether and how long-term financial trends may have modified the transmission mechanism from monetary policy decisions to economic activity. The focus is on longterm changes, abstracting from the disruptions created by the 2007-08 financial turmoil which are temporarily affecting the transmission mechanism. The first series of findings is that a number of factors have worked to strengthen the transmission of monetary policy, including more competitive financial markets, higher household indebtedness, greater diversity in the supply of financial products, greater financial integration and more responsive asset pricing mechanisms. However, other factors appear to have simultaneously gone in the direction of weakening transmission of domestic policy, including greater external financial influences, lower exchange-rate pass-through and a broad-based shift towards fixed-rate assets and liabilities. On balance, monetary policy appears to remain a powerful tool for guiding aggregate demand, but a number of changes that have worked to support the strength of transmission have also increased risks to financial stability